O Programa de Medidas Socioeducativas em Meio Aberto : educação ou reprodução do aprendizado da rua? - Quinelatto, Rubia Fernanda (2015)
This research focuses on looking at the life trajectory of young people in conflict with the law living in the county of São Paulo-SP, which introduces new forms of performance of socially marginalized youths, questioning stereotypes that associate youth action violence, transgression, drugs, trafficking, political indifference, resignation for alleged public space and school. The focus is to dialogue with the stories of life young in conflict with the law in seeking to understand what meaning they attach to the offender act, for it were asked 15 young collaborators for interviews within the Program Socio-Educational measures in Half Open. The life stories narrated by young in conflict with the law were initially transcribed verbatim, and subsequently textualized finally transcriadas. The theoretical and methodological rationale was based on studies by José Carlos Sebe Bom Meihy, coordinator of the Center for Studies in Oral History of USP (NEHO). The research used pivotably Oral History of Life and thematic oral history, highlighting the stories of fragments young with the aim of understanding the social context to which they belong, playing educational processes seized, the place for the school and informal work. The transcreation allows inaugurate a process of creation and dialogue with lives (re)created in narratives. Thus, the main theorists were prioritized Michel Maffesoli, Áurea Maria Guimarães, Marisa Feffermann, José Carlos Sebe Bom Meihy, Alberto Lins Caldas. Such authors show the uniqueness of the stories of lives that are intertwined with other stories within practices, historically and culturally developed, providing new forms of relationship. The street learning stands out as a possible way for these young people as a result of numerous failures of public policies.